Motorcycle accident model for highlands regions by applying Generaliazed Linear Model (GLM) - Sobri Abusini; L Ambarwati (Lowland Technology International, 2018)
Motorcyclists are the major victims in highway accidents due to instability of motorcycle vehicle and driver behavior. Currently, insufficient studies related to motorcycles accident model considering road geometry and traffic characteristics in highland regions were conducted. This study carried out the investigation on crashes involving motorcycle, development of motorcycle accident model for highland regions of Malang City, East Java Province as a case study. The research analysis employed the Generalized Linear Model (GLM). The model was developed by using accidents data from Police Department and investigation of traffic and road geometry as black spots. On ten road sections investigated and distributed questionnaires to 100 respondents, the respondents experience 1-2 times accidents with light injuries (26%) and serious injuries (11%), and no injury (3%). Accidents occur at noon (11%) and afternoon (13%) and due to their own fault and crashing with other motorcycle (27%). The results are found out that motorcycle accident model influenced by traffic factors, i.e. flow and speed and also road geometric factors, i.e. lane width (LW), shoulder width (SW), number of lanes (NL), number of access roads (NA) and walkway width (WW).